Causes and Consequences of Intraspecific Variation in Nesting Behaviors: Insights from Blue Tits and Great Tits - Mainwaring, Mark C. (Frontiers in Ecology and Evolution, 2017)
Nest building is an important and yet under-studied stage of the reproductive cycle in many taxa, including birds, and whilst we have a decent understanding of interspecific variation in avian nesting behaviours, our understanding of intraspecific variation in nesting behaviours is much less developed. This is largely because an insufficient number of studies have been performed on any one species to draw robust conclusions. Fortunately, though, the amount of research on the nesting behaviours of nestbox-breeding blue tits (Cyanistes caeruleus) and great tits (Parus major) has increased dramatically in recent years and their nesting behaviours are now sufficiently well studied to offer useful insights into intraspecific variation in avian nesting behaviours. Studies show that individuals of both species select nest sites based on the presence and/or absence of conspecifics and heterospecifics and whilst neighbours were assumed to adversely affect focal individuals by competing for resources, they are now considered beneficial as they provide information about habitat quality and contribute to anti-predator defences. Nest-building females accurately gauge local weather conditions and respond to predictable variation in environmental conditions by building nests with variable amounts of cup lining material to create suitable nest microclimates for nestlings. Meanwhile, both species vary the amount of aromatic plant materials in their nests in relation to the abundance of nest-dwelling parasites and pathogens and as aromatic plant materials also play a role in sexual selection then nest materials can have multiple functions. The height of nests is negatively correlated with the local risk of predation but whilst predator avoidance favours lower nests, sexual selection favours taller nests. In fact, higher quality females build taller nests that contain more green plant material which in turn influences the amount of care provided by males. This suggests there is considerable intraspecific variation in nesting behaviours in blue and great tits, and in birds generally, and highlights that birds are adept at adaptively varying their nesting behaviours in response to multiple factors. There is, however, a paucity of evidence directly linking such variation in nest building behaviours to reproductive success or fitness more broadly and so further studies could usefully